The Effect of Parents’ Education on Students’ Learning Achievement - Somadayo, Samsu (International Journal of Psychosocial Rehabilitation, 2020)
The effect of parents’ education level on students’ achievement is the focus of the present research. It is based on the fact that the success of education is determined by several factors. One of them is parents. Parent provide the first and foremost education for the child to achieve the purpose of life. The purpose of this study is to know the effect of parents’ education level on student achievement. This research, conducted at SMP Negeri 4 of Kayoa District, involved 83 students and 73 parents. The data of this research include the data of parents’ education level and students’ learning achievement. The data of students’ achievement were analyzed using percentage technique. The results showed that 1) parents’ level of education in SMP Negeri 4 of Kayoa District, in general, is still low, and that 2) parents’ education level has a very close relationship with student achievement.